2020
DOI: 10.4081/aiua.2019.4.251
|View full text |Cite
|
Sign up to set email alerts
|

The association of Boswellia resin extract and propolis derived polyphenols can improve quality of life in patients affected by prostatitis-like symptoms

Abstract: Objectives: Chronic prostatitis syndrome is a bothering and poorly understood condition. Many patients report genitourinary pain and Lower Urinary Tract Symptoms as a main complaint. Many different pharmacological or behavioural therapies are prescribed in daily clinical practice, but efficacy data are still lacking. The aim of our study was to test the efficacy and safety of a transrectal delivered association of Boswellia resin extract and propolis derived polyphenols for the relief of prostatitis - like sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Boswellia has been traditionally considered as a potential therapeutic option against several chronic inflammatory diseases, such as chronic prostatitis and chronic pelvic pain syndrome. Moreover, Sibona et al recently demonstrated the clinical efficacy of a phytotherapeutic agent containing boswellia in the management of patients affected by prostatitis-like symptoms, showing a significant enhancement of symptoms relief [25]. Similarly, several authors reported clinical benefits of a curcumin supplementation on main functional parameters related to prostatic diseases [26,27], such as pain relief [27].…”
Section: Results In Comparison With Other Studiesmentioning
confidence: 97%
“…Boswellia has been traditionally considered as a potential therapeutic option against several chronic inflammatory diseases, such as chronic prostatitis and chronic pelvic pain syndrome. Moreover, Sibona et al recently demonstrated the clinical efficacy of a phytotherapeutic agent containing boswellia in the management of patients affected by prostatitis-like symptoms, showing a significant enhancement of symptoms relief [25]. Similarly, several authors reported clinical benefits of a curcumin supplementation on main functional parameters related to prostatic diseases [26,27], such as pain relief [27].…”
Section: Results In Comparison With Other Studiesmentioning
confidence: 97%
“…Indeed, one of the most important etiological agents of inflammatory diseases is the cause-and-effect relationship between oxygen free radicals and oxidative damage at the biomolecular level [ 26 28 ]. Actually, the efficacy of the transrectal delivered association of Boswellia resin extract and propolis derived polyphenols in relieving prostatitis-like symptoms was tested by another research group [ 29 ]. As assessed by standardised questionnaires, the suppository was found able to reduce genitourinary pain and to improve quality of life in men affected by bothersome prostatitis-like symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Other indications for such devices include promotion of fertilization [27], delivery of anti-HIV drugs [28], etc. Medical devices in the form of rectal suppositories, creams, and gels are used for treatment and prevention of proctological and urological diseases [29,30]. In view of this, our medical-scientific justification of classification of the studied products as medical devices is harmonized with regulatory bodies practice (Conformity Assessment Body) of the European Union countries.…”
Section: Discussionmentioning
confidence: 99%